Time to kill : a sniper novel - Coughlin, Jack, 1966- (Coughlin, Jack, 1966- Sniper novel., 2013)
When the Sphinx is blown up by terrorists who also launch attacks on an Iranian soccer team and a vessel in the Red Sea, Kyle Swanson and his Trident team uncover an extremist plot to provoke war between Egypt and Iran to upset the balance of international power.